(untitled) (Revista Española de Fisiología, 1971)
From a biochemical point of view, we think that inhibition of adenosin-desaminase by adenine-nucleotides represents a cybernetic mechanism, a positive feed-back wich could act as a regulator of this nucleotides syntesis. From a physiologycal point of view, we postulate that the role atributed to adenine- nucleotides as regulators of coronary flux may be mediated through adenosine, as results of inhibition of adenosin-desaminase, enzyme wich provides the hydrolitic deamination of the nucleoside. In tire present paper it has been studied the kinetics of the inhibition of adenosin- desaminase by adenine-nucleotides. The amount of inhibition finded was 8. 12 and 25 % for concentrations of 0.08 mM of AMP, ADP and ATP respectively, and 23, 26 and 40 % for concentrations of 0.16 mM. Present findings accord with values of Ki of 0.024 mM for ATP, 0.032 mM for ADP and 0.038 mM for AMP. We suggest that this may be due to the influence of the phosphoric chain on the affinity of the enzyme for each nucleotide.